Negative range size–abundance relationships in Indo‐Pacific bird communities. Issue 10 (16th December 2015) - Reeve, Andrew Hart; Borregaard, Michael Krabbe; Fjeldså, Jon
Abstract : The positive relationship between range size and abundance is one of the best‐documented patterns in macroecology, but a growing number of studies from isolated tropical areas have reported negative or neutral relationships. It has been hypothesized that the combination of geographic isolation and environmental stability create selection pressures that favor narrowly specialized species, which could drive these non‐positive relationships. To test this idea, we measured the range size–abundance relationships of eleven bird communities in mature and degraded forest on four islands in the Indo‐Pacific, namely Flores in the Lesser Sundas, Seram in the Moluccas, and the New Caledonian islands of Grande Terre and Lifou. Local abundance data was gathered through extensive and methodologically consistent surveying, and regressed against global range size using linear mixed effect models. The relationship between range size and abundance was significantly negative across all combined mature and degraded forest communities. As negative relationships were found in degraded forest with little environmental stability, we conclude that the abundance of small‐ranged species on the study islands cannot be ascribed to narrow specialization. Rather, cross‐habitat community comparisons indicate that locally abundant endemic and near‐endemic species adapted to a broad spectrum of local environmental conditions cause the observed negative relationships. We suspect that geographic isolation facilitates the evolution of species that are simultaneously broad‐niched, small‐ranged, and abundant, as water barriers limit the range expansions that would typically accompany species' attainment of high local population densities. The consistently negative relationships found across Indo‐Pacific islands represent a striking deviation from the positive range size–abundance relationship 'rule', and future studies should seek to determine whether the patterns detected here extend to geographically isolated mainland environments.